PENGARUH REGULASI EMOSI TERHADAP COPING PENYELESAIAN STUDI MAHASISWA - Anwar, Amanah (Jurnal Psikologi, 2018)
AbstractCompletion of studies on time students need coping, namely the process of self-management in a cognitive and continuous behavior that is strived to exceed the demands of the environment externally and internally. Cognitive self-management is done by controlling one's emotions. Emotional regulation involves awareness that can be managed from an unconscious process to become more aware. Rhythmic breathing in exercise can regulate emotions to be stable and can last longer. This study aims to determine the effect of emotional regulation on coping in the completion of student studies. Participants were 66 students (10 faculties, 8 study programs, at X private universities in West Jakarta). The sampling technique used is probability sampling with proportional stratified random sampling. The measuring instrument adapted from the Way of Coping Questionnaire from Lazarus (1992), and the revision of the Difficulties in Emotion Regulation Scale (DERS) from the Institute for Research and Measurement of the Faculty of Psychology, Tarumanagara University, Jakarta. The results of regression analysis with ANOVA test on the variables of emotion regulation and coping completion of the study after doing gymnastics showed that there was a significant effect of emotion regulation on coping completion of the study (F = 11,192 p <0.01). Emotional regulation contribution to the completion of study coping was 14.9% while the remaining 85.1% was influenced by other factors (R Square = 0.149). The results of the regression analysis of the t test showed that there was a significant effect of emotional regulation on coping with the completion of the study (t = 3.345, p <0.01). However, the significant and positive influence (Beta = +0,386) of emotional regulation on coping with the completion of the study must be interpreted with caution. Keywords: emotion regulation, coping study completion, student. AbstrakPenyelesaian studi tepat waktu mahasiswa memerlukan coping, yaitu prosespengelolaan diri secara kognitif dan perilaku terus menerus yang diupayakan untuk dapat melebihi tuntutan lingkungan secara eksternal dan internal.Pengelolaan diri secara kognitif dilakukan dengan mengendalikan emosi seseorang.Regulasi emosi melibatkan kesadaran yang dapat mengatur dari proses yang tidak disadari menjadi lebih disadari. Pengaturan napas secara ritmik dalam senam dapat mengatur emosi menjadi stabil dan dapat bertahan lebih lama.Penelitian ini bertujuan mengetahui pengaruh regulasi emosi terhadap coping penyelesaian studi mahasiswa. Partisipan adalah 66 mahasiswa (10 fakultas,8prodi, pada perguruan tinggi swasta X di Jakarta Barat). Teknik pengambilan sampel yang digunakan adalahprobability sampling dengan proporsional stratified random sampling.Instrumen ukur adaptasi dari the Way of Coping Questionnairedari Lazarus (1992), dan revisi Difficulties in Emotion Regulation Scale (DERS) dari Lembaga Riset dan Pengukuran Fakultas Psikologi Universitas Tarumanagara Jakarta. Hasil analisisregresidenganuji Anova terhadap variabelregulasi emosidancoping penyelesaian studisetelah melakukan senam menunjukkan terdapat pengaruh yang signifikan dari regulasi emosi terhadapcoping penyelesaian studi (F = 11.192 p < 0.01). Sumbangan regulasi emosi terhadap coping penyelesaian studi sebesar14.9 % sedangkan sisanya 85.1 % dipengaruhi faktor lain(R Square= 0.149). Hasil analisis regresi uji t menunjukkan terdapat pengaruh yang signifikan dari regulasi emosi terhadap coping penyelesaian studi (t = 3.345, p < 0.01). Walaupun demikian, pengaruh signifikan dan positif (Beta = +0,386) dari regulasi emosi terhadap coping penyelesaian studi harus diinterpretasi secara hati-hati. Kata-kata kunci:regulasi emosi,coping penyelesaian studi, mahasiswa.